NANOSTRUCTURED LIPID CARRIERS: A NEXT-GENERATION LIPID-BASED DELIVERY SYSTEM - Ms. Sandhyarani Sagavkar; Dr. Kishor Gujar (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Background: Nanostructured Lipid Carriers (NLCs) are advanced lipid-based nanocarriers developed to address the limitations of Solid Lipid Nanoparticles (SLNs), such as low drug loading and drug expulsion during storage. The inclusion of both solid and liquid lipids in NLCs leads to a disordered internal matrix either imperfect or amorphous enhancing drug entrapment, stability, and enabling controlled drug release. Objectives: This review aims to evaluate the classification, composition, preparation methods, and pharmaceutical potential of NLCs. It emphasizes structural types (imperfect, amorphous, and multiple-type NLCs), their critical components (solid lipids, liquid lipids, surfactants), and their mechanisms for improving drug delivery and bioavailability. Methodology: A literature-based analysis is conducted to review various formulation strategies and preparation techniques for NLCs. Key physicochemical parameters such as particle size, polydispersity index (PDI), zeta potential, and drug encapsulation efficiency are discussed in terms of their impact on formulation performance. Expected Outcomes: NLCs are shown to enhance bioavailability through improved solubility, increased permeability across skin and mucosal barriers, and lymphatic uptake. Their biodegradability, scalability, and ability to support site-specific delivery make them suitable for oral, topical, transdermal routes. Conclusion: NLCs offer significant potential as next-generation drug delivery systems. While challenges such as cytotoxicity and surfactant-related hypersensitivity exist, ongoing innovations in lipid selection and formulation highlight their growing role in advancing pharmaceutical delivery for a wide range of therapeutic agents.